Criação e implementação do jogo desafio urbano : contribuições para o ensino-aprendizagem de geografia - Verri, Juliana Bertolino (2017)
When working with any educational process of human beings in general and particularly in Geography, it is necessary to question the strategies of teaching to utilize, always seeking those that allows developing with dynamism contents and skills associated with them which provides students conditions to gradually develop a geographical view of the world. In other words, appropriating of theoretical and practical references of this science can share in an experiential and collaborative way to the knowledge and skills. In this context, the present research aims to analyze the process of development, implementation and evaluation of a didactic board game focused on contents of Urban Geography entitled "Urban Challenge". We seek, according to the presuppositions of the specific didactics in general, and particularly of the didactics of Geography, to articulate the epistemological and methodological peculiarities of the school discipline to pedagogical. We understand that didactics - and by extension the effectiveness of a didactic resource - only makes sense if connected to the scientific logic of the discipline that is taught. The didactic investigation has corresponded to an in class action-research of the 7th grade students of elementary school, from the private school network, in the city of Maringá-PR. To subsidize this study, we've proceeded to a data survey - observations of teachers which applied the game and questionnaires answered by student-players. The study evidenced that the application of the Urban Challenge game is a positive alternative to subsidize the teacher in the teaching-learning process, in special, for a discipline of Geography, providing to students a relaxed and a relaxed environment full of knowlege. In this direction, the work also aimed to contribute on the deepening of the studies towards the didactics, with the focus on Geography didactic in what concerns the correlation Geography and teaching of Urban Geography.